Pengaruh Karakteristik Event terhadap Keputusan Berkunjung di The Kaldera Nomadic Escape Studi Kasus : Event Marende Fest 2024 - Wardani, Alvia Rahma; Benazira, Aulia; Anggreini, Nella (Abdimas Indonesian Journal, 2024)
The Caldera Nomadic Escape is a tourist destination developed by the Ministry of Tourism through the Lake Toba Authority Implementing Agency (BPODT). This research aims to determine the influence of event characteristics on the decision to visit domestic tourists at The Kaldera Nomadic Escape case study: Marende Fest 2024 event. The population of this study was 2,463 and the sample used was 100 respondents. The sampling technique used was nonprobability sampling with purposive sampling technique. This research uses quantitative research methods with a descriptive research type which includes validity testing, reliability testing, classical assumption testing and hypothesis testing. The results of this research are (1) the uniqueness variable has a partial and significant influence on the decision to visit with a calculated r value of 3.618, (2) ) the perishability variable has a partial influence on the decision to visit with a calculated value of 6.663, (3) the variable Intangibility has a partial influence on the decision to visit with a calculated value of 4.998, (4) the atmosphere and service variables have a partial influence on the decision to visit with a calculated value of 7.807 , (5) the personal interaction variable partially influences the decision to visit with a calculated r value of 6.738. The results of this research from the variables of uniqueness, perishability, intangibility, atmosphere and service, personal interactions together (simultaneously) have a positive and significant influence. The research results of the Coefficient of Determination (R2) show that the variables of uniqueness, perishability, intangibility, atmosphere and service, personal interaction are able to influence visiting decisions by 89% and the remaining 11% is influenced by variables not examined in this research.